Life Cycle Assessment and Carbon Footprint Optimisation of AgrivoltaicSystems Combining Bifacial Solar Panels with Drip-Irrigated VegetableProduction in Semi-Arid Mediterranean Climates (Aintelia Science Notes, 2025)
Agrivoltaic (AV) systems co-locate solar photovoltaics and agriculture, offering a high-impact strategy for the food-energy-water nexus in semi-arid Mediterranean regions. This paper presents a 25-year cradle-to-gate Life Cycle Assessment (LCA) of a 2 ha AV system in Beja, Tunisia, combining elevated bifacial PERC panels with drip-irrigated tomato and pepper production. Using ReCiPe 2016 (midpoint H) and ecoinvent 3.9, three configurations are compared: conventional open-field cropping (C1), fixed-rate drip AV (C2), and precision drip AV with soil sensors (C3).The C3 configuration achieves a Global Warming Potential (GWP) of 42.3 g CO₂-eq/kWh, which is 92% lower than the Tunisian grid (527 g CO₂-eq/kWh) and 18% below standard ground-mount PV. Driven by shading-induced evapotranspiration reduction and sensor scheduling, C3 reduces seasonal water consumption by 33.4% compared to C1. Its Land Equivalent Ratio (LER) of 1.42 confirms a 42% land-use efficiency gain over separate monocultures. Additionally, the elevated geometry enables an 8.3% bifacial rear-face irradiance gain, boosting energy yield by 4.1%. These findings provide a quantitative evidence base for Mediterranean AV policy.
Keywords: Agrivoltaic; Carbon Footprint; Bifacial Solar Panel; Drip Irrigation